QoV: Assessing the monitoring quality in visual sensor networks - Daniel G. Costa (2012)
Camera-enabled sensor nodes deployed for visual monitoring can considerably enlarge the applicability of wireless sensor networks. Due to the stringent requirements of visual data transmission and processing, when compared with scalar wireless sensor networks, quality assessment becomes a relevant issue. Although academic investigation has been focused on QoS parameters such as end-to-end delay, throughput and packet error rate, what is being seen by source nodes may be more important for the application than the quality of received data. In such way, we propose the novel concept of Quality of Viewing (QoV) to be employed as an important QoS parameter when assessing the monitoring quality in visual sensor networks. Some issues for the establishment of the QoV of monitoring applications will be presented, as well as practical exploitation of this parameter for dynamic verification, control and management of wireless sensor networks composed of camera-enabled source nodes. Â(c) 2012 IEEE.